Escherichia coli lipopolysaccharide; a better alternative therapy of endometritis in crossbred cows - SHAKTAWAT, J S; SAXENA, M S; PRASAD, J K; SINGH, C P; JHAMB, DINESH (The Indian Journal of Animal Reproduction, 2023)
Intrauterine therapy with 100 μg £. coli LPS was evaluated for its therapeutic efficacy in crossbred cows withendometritis and was compared with conventional antibiotic therapy based on in-vitro antibiogram. At pre-treatment andpost-treatment estrus, estrual cervical mucus was studied for change in appearance, white side test, pH and bacterial load. Theconception rate was high in LPS group (71.43%) followed by antibiotic group (57.14%) with low conception rate in controlgroup cows (28.52%). Hence, it is concluded that intrauterine infusion of 100 μg E.coli LPS is a better alternative toconventional antibiotic treatment in cows with endometritis.
Keywords: E. coli LPS; in-vitro antibiogram; estrual cervical mucus; white side test; pH; conception rate